The mechanism of potentiation of horseradish peroxidase-catalysed oxidation of NADPH by porphyrins. - Van Steveninck, J (1987)
Several porphyrins, including HpD (haematoporphyrin derivative), potentiate the oxidation of NADPH by horseradish peroxidase/H2O2. To elucidate the mechanism of potentiation, the following observations are relevant. During peroxidase-catalysed NADPH oxidation, O2-.(superoxide radical) is generated, as judged from superoxide dismutase-inhibitable cytochrome c reduction. This generation of O2-. is suppressed by HpD. Peroxidase-catalysed NADPH oxidation is stimulated by superoxide dismutase and by anaerobic conditions. Under anaerobic conditions HpD has no influence on peroxide-catalysed NADPH oxidation. Previous studies have shown that horseradish peroxidase is inhibited by O2-.. Thus the experimental results indicate that the potentiating effect of HpD can be explained by its ability to inhibit O2-. generation in the horseradish peroxidase/H2O2/NADPH system.